The Impact Of Tourism Development On The Economic Condition Of The Community In The Sigandu Beach Area, Batang Regency - Nova Karisma (Robust: Research of Business and Economics Studies, 2023)
Sigandu Beach is a tourist destination in Batang Regency that has grown over time and significantly impacted the local economy. The study aimed to determine (1) the impact of tourist development on the surrounding community and (2) the impact of tourism development on the surrounding community. (2) After the development, the community's impression of the economy. This study employs a qualitative descriptive technique, with data gathered from in-person interviews and supplemented with articles and journals relating to the study's theme. The study's findings reveal that (1) tourist growth positively impacts the surrounding community by raising income, giving work possibilities, and encouraging the community to expand business. (2) good perception of the community toward tourism development because it positively impacts the surrounding community.